Factors affecting the income of capture fishermen in Kijang Kota Sub-district, Bintan Regency - Adani, Annisa Nabilah; Tetty, Tetty; Ulfah, Fitria (Politeknik Negeri Sambas, 2024)
Fishermen have a very low income. Fishermen's income generally comes from catches sold, and is influenced by various other factors. The factors that can affect income that become variables in this study are capital factors, fish selling prices, working hours, fishing gear, and experience. The purpose of this study was to determine the effects of capital factors (X1), selling price of fish (X2), working hours (X3), fishing gear (X4), and experience (X5) on income (Y). The research location is Kijang Kota Village, Bintan Regency from December to 2022-January 2023. Sampling was performed by simple random sampling, with 42 respondents using the slovin technique. Data were collected using observations, questionnaires, and interviews. Data analysis was performed using multiple linear regression analysis with SPSS 27 software. The results show that the variables that affect income are selling price, working hours, and fishing gear. The variables that had no effect were capital and experience. The results of the simultaneous test show that the independent variables used in the study have a positive effect on the income of captured fishermen.